2021
DOI: 10.1021/acs.chemmater.1c01755
|View full text |Cite
|
Sign up to set email alerts
|

Fast Water-Assisted Lithium Ion Conduction in Restacked Lithium Tin Sulfide Nanosheets

Abstract: While two-dimensional (2D) materials may preserve some intrinsic properties of the corresponding layered bulk material, new characteristics arise from their pronounced anisotropy or confinement effects. Recently, exceptionally high ionic conductivities were discovered in 2D materials such as graphene oxide and vermiculite. Here, we report on the water-assisted fast conduction of lithium ions in restacked lithium tin sulfide nanosheets. Li0.8Sn0.8S2 exfoliates spontaneously in water and can be restacked into ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…[ 95a ] A variety of ions can be effectively channelled (e.g., H + , Li + , Na + , K + , Ca 2+ , Al 3+ , OH − ). [ 95a,97b,99 ] At the same time, the individual transport properties can be tailored by choice of the respective 2D material constituting the channels. The surface characteristics of the channel mainly govern the transport properties.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 95a ] A variety of ions can be effectively channelled (e.g., H + , Li + , Na + , K + , Ca 2+ , Al 3+ , OH − ). [ 95a,97b,99 ] At the same time, the individual transport properties can be tailored by choice of the respective 2D material constituting the channels. The surface characteristics of the channel mainly govern the transport properties.…”
Section: Applicationmentioning
confidence: 99%
“…[ 101 ] While conventional methods employing lithography or sacrificial agents are time‐consuming and offer limited possibilities to tailor the nature of the channels, the wide variety of 2D materials and versatility of the 1D dissolution approach enables tailoring of each of these properties individually. Superionic transport in reconstructed channels has been demonstrated for a variety of 2D materials, including GO [ 97b ] (H + , K + , Ca 2+ ), vermiculite [ 96 ] (H + ), LDHs [ 95a ] (OH − ), boron nitride [ 101a ] (H + , K + , Na + ), and MXenes [ 99c ] (H + , Na + , K + , Al 3+ ).…”
Section: Applicationmentioning
confidence: 99%
“…Hydration–dehydration plays an important role in altering the fundamental physical properties of solids, especially in alkali metal-containing non-van der Waals (non-vdW) 2D materials. Non-vdW solids containing Li and Na ions have the propensity to intercalate water due to the high enthalpy of hydration of these two alkali ions . As a consequence of this hydration–dehydration, often, the individual layers restack reversibly or there is an increase in the interlayer distances or complete exfoliation of layers, leading to changes in the properties. These property changes can be as exotic as the change of superconducting transition temperature ( T C ) and more common phenomena as the change of ionic conductivity of the interlayer alkali ions as a function of hydration. , Note that the incorporated water molecules into the crystal structure especially into the oxide framework may undergo dissociation, leading to enhancement of proton ion conduction. ,, Recently, Lotsch’s, zur Loye’s, and our groups have found that such hydration–dehydration phenomena are more prevalent in Li- and Na-intercalated layered chalcogenides, which in addition to showing some interesting properties also possess challenges in crystal structure determination of both hydrated and dehydrated phases as a result of the stacking fault and preferred orientations. ,,− Lotsch’s group has demonstrated the impact of hydration on Li-ion conductivity, while our group has demonstrated that in NaGaS 2 , Na-ion conductivity increases many times in the hydrated phase . In addition to ionic conductivity, the ability of selective absorption of water from solution and vapor makes NaGaS 2 a unique material that can selectively trap water from the atmosphere and in a mixture of solvents.…”
Section: Introductionmentioning
confidence: 99%
“…We compare Li ion conductivity between the Ti 0.88 O 2 0.48– membrane with those of previously reported Li ion conductive materials in the presence of water (Figure c and Supplementary Table 1). The Li ion conductivity in this work is 0.21 and 0.62 S cm –1 at 25 °C and 90 °C, respectively, which is 1–3 times higher than most start-of-the-art Li ion conductive materials. …”
mentioning
confidence: 65%